KEMAMPUAN KONEKSI MATEMATIS SISWA DALAM PEMBELAJARAN PROJECT BASED LEARNING DENGAN PENDEKATAN PMRI DITINJAU DARI SELF-EFFICACY - Putri, Wahyu Ananda; Zaenuri, Zaenuri; Kartono, Kartono (ANARGYA: Jurnal Ilmiah Pendidikan Matematika, 2024)
Several things that are important in learning connected mathematics, namely mathematics and self-ability, can be developed using the PjBL learning model with the PMRI approach. The aims of this research are (1) to analyze the quality of the PjBL learning model using the PMRI approach in junior high schools and (2) to find patterns of mathematical connection abilities of class VII SMP students in terms of self-ability. This research method is a mixed method with a mixture of qualitative and quantitative research. Class VII students of SMP Negeri 2 Banyubiru are the population in this study. The research sample was taken using random sampling technique. This research data was collected using observation, tests, documentation, interviews and questionnaires. This research obtained the results that the PjBL model with the PMRI approach has good quality for improving students' mathematical connection abilities as evidenced by the posttest results of students who achieved minimum completeness and the proportion of completeness was more than 75%. Subjects with high self-efficacy are able to fulfill all mathematical connection indicators. Subjects with moderate self-efficacy can also master all indicators but are still not good. Low student self-efficacy cannot master mathematics indicators in contexts outside mathematics. So the higher the student's self-efficacy, the higher their mathematical connection ability will be